Gestational Weight Gain Below the 2009 Institute of Medicine Guidelines Modifies Preterm Birth in Obese Pregnant Women [321]. (May 2015) - Berger, Alexander A.; Levitan, Gila; Baxter, Jason K.; Lerner-Geva, Liat
Abstract : INTRODUCTION: Obesity and excessive gestational weight gain present significant challenges during pregnancy to the mother and neonate, including an increased rate of preterm birth, the leading direct cause of neonatal death. The Institute of Medicine (IOM) refined guidelines for appropriate gestational weight gain in 2009 to improve outcomes for all mothers. Recent research suggests the gestational weight gain recommendations for obese mothers may be too high, leading to increased preterm birth. We conducted a systematic review to evaluate the effect of gestational weight gain below the IOM guidelines on preterm birth for obese pregnant women. METHODS: PubMed, Cochrane, CINAHL, and EMBASE were systematically searched from inception to 2014 for relevant articles; previous reference lists were reviewed and authors and experts were queried to find other relevant studies. Two reviewers independently reviewed 116 abstracts and 38 full-text articles to identify seven studies that reported for obese pregnant women, gestational weight gain, and its effect on the rate of preterm birth. RESULTS: Overall, the included evidence was of fair to good quality. There is low certainty in the evidence for overall preterm birth, insufficient evidence for preterm birth subtypes, and moderate certainty for both teenagers and African Americans for gestational weight gain below the 2009 IOM recommendations increasing preterm birth rates for obese pregnant women. There is low certainty in the evidence that obesity class modulates this effect. CONCLUSION AND IMPLICATION: Gestational weight gain below the 2009 IOM recommendations may increase preterm birth rates for obese pregnant women. Evidence with moderate strength suggests that teenagers and African Americans show this effect.